Synthesis of Zinc Oxide (ZnO) Nanoparticles Using Microwave Assistance and Its Application as Photocatalyst in Degrading Methylene Blue - Wahyu Firmansya Nursalam; Lidya Irma Momuat; Henry Fonda Aritonang (Jurnal Kimia Sains dan Aplikasi, 2023)
The research has been carried out on synthesizing zinc oxide (ZnO) nanoparticles with the help of microwaves. ZnO nanoparticles were synthesized in the microwave at 100°C with heating times of 50, 90, 130, 170, and 210 minutes. The synthesized ZnO nanoparticles were characterized using X-Ray Diffractometry (XRD) and Energy Dispersive Spectroscopy (EDS). The results were analyzed for their ability as a photocatalyst against methylene blue (MB) solution using UV-Vis spectrophotometry. The results revealed that the synthesized product was a combination of ZnO and Zn(OH) 2, as supported by XRD ICSD data no. 31052. However, the analysis results with EDS showed that the synthesized product only contained Zn and O elements, indicating that the product had ZnO. ZnO nanoparticles synthesized for 170 minutes of heating showed the highest ability to degrade MB of 85.8247% with a contact time of 150 minutes, while heating times of 50, 90, 130, and 210 minutes had percentage of MB degradation of 84.6065%, 81.0130%, 82.0866%, and 82.9275%, respectively.